EDUPRENEURSHIP BERWAWASAN INDUSTRI DAN PARIWISATA DALAM MENDUKUNG TATA SOSIAL MASYARAKAT MARJINAL - Iin Purnamasari; Suwarno Widodo; Pipit Mugi Handayani; Dwi Prastyo Hadi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to map the social, economic and environmental potential of the people of Tegalrejo Village and to find the potential that is expected to be a solution to problems in the Tegalrejo environment.The research method used is qualitative with an ethnographic approach. Primary data obtained from the results of in-depth interviews. The secondary data was obtained from filling out questionnaires, Focus Group Discussions/FGDs and documentation studies. Participant observations were also carried out to collect data related to the views of the assisted women on social, economic and environmental arrangements. Meanwhile, the documentation study was used to map the potential of the community in the Tegalrejo environment, Jatijajar village, which is related to social, economic and environmental arrangements. Data analysis was carried out by looking for cultural themes, namely domain analysis, followed by taxonomic analysis, and componential analysis. Furthermore, an analysis of cultural themes that link social, economic and environmental cases in the Tegalrejo area is carried out.The results of the study found that the social potential of the Tegalrejo community was to have a harmonious and peaceful nature, then care for each other, then be compact and never have conflict. There are local values that can be developed for the advancement of the Tegalrejo environment such as mutual cooperation, cultural arts, special foods, and production in the tourism industry. The economic potential that can be developed is the formation of MSMEs with types of processed food and types of stall trading, types of services, types of online trade, types of online trade, MSME Tourism, beauty salons and bridal makeup and general markets. Environmental potential, Tegalrejo can be developed into a rest area and display area for MSME products, a culinary center typical of Tegalrejo, an arts and culture area as well as a parking center for industrial areas and a public center in the Tegalrejo neighborhood.